Meningkatkan Pemahaman dan Sikap Peserta Didik Terhadap Konsep Gereja yang Satu, Kudus, Katolik, dan Apostolik Melalui Model Pembelajaran Problem Based Learning - Hendri Hendri (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study aims to improve students' understanding and attitudes toward the concept of One, Holy, Catholic, and Apostolic Church through the Problem Based Learning (PBL) model. The background of this research is the low level of students' understanding of the Church concept due to conventional teaching methods that are less engaging and do not provide direct learning experiences. This study employs the Classroom Action Research (CAR) method using the Kemmis and McTaggart model, conducted in two cycles at SDN 16 Sanjan Emberas. Data collection techniques include observation, interviews, tests, and reflective journals. The findings indicate that implementing the PBL model increased students' average scores from 55 in the first cycle to 83 in the second cycle. Additionally, students became more active in discussions, were able to relate the Church concept to daily life, and demonstrated positive attitudes such as cooperation and involvement in the Church community. Supporting factors for the successful implementation of PBL include students' enthusiasm, teacher and school support, and adequate learning resources. Challenges encountered include time constraints and varying levels of student understanding. This study concludes that the PBL model is effective in enhancing students' comprehension and attitudes toward the Church concept, making it a viable alternative teaching strategy for Catholic Religious Education.